Inovasi Media Promosi Sekolah guna Pengembangan Website sebagai Strategi Pemasaran SMK Islam As-Syarief - Untung Novianto; Ai Salsabila (Politeknik Piksi Ganesha Indonesia, 2026)
This community service activity focused on strengthening digital promotion capacity through website development as a school marketing medium. The main challenges faced by partners were limited effective promotional media, low digital visibility, and the suboptimal use of information technology to attract prospective students. The objective of this activity was to increase school competitiveness through innovative website-based promotional media integrated with digital marketing strategies. The method used was Participatory Action Research, which emphasized active collaboration between the implementation team and the school. The results of the activity demonstrated improved digital content management capabilities and significantly increased the reach of school promotions.